Risk Analysis and Pricing of Retail Energy Contracts - Hron, Jiří; Marek, Luboš; Málek, Jiří, 1953-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2014)
The presented dissertation is focused on the applications of statistical methods and ap-proaches applied in the energy business. The need for the modeling of energy risks arose only recently when the energy business was opened to competition. Therefore, the prima-ry aim of the dissertation is to clarify the main principles of the energy business which are necessary for understanding both risk principles and motivation of the proposed models. I am largely focused on retail risks, i.e., the risks associated with delivery to end-consumers. In particular, I deal with energy contracts providing volume flexibility, recalled as swing options in the literature. Therefore, the second issue on which I am focusing is a group of demand-driven swing options whose more systematic analysis in the portfolio context has not been published so far. Examining the risk, I apply the deductive (probabil-istic) analysis which reveals interesting relations between correlations. The practical ap-plications also require inductive considerations resulting in the construction of statistical estimators relying on historical data. I propose an estimator of the volumetric correlation based on a classical theory whose bias is investigated via MC simulation. To analyze a par-ticular volume-price correlation, I introduced the notion of robust dependency. Applying bootstrap procedures, robust dependency can be used both for testing purposes and for sensitivity analysis of the sample correlation. There are many works available devoted to energy price models which are different from the price models applied on financial markets. Therefore, the third target of the dis-sertation is an empirical statistical analysis of both power and natural gas Czech spot pric-es which can serve as a basis for the development of price models adapted to the Czech market environment. Finally, the fourth aim is the evaluation of power contracts which is very specific.
The outputs of the model are both a synthetic market price and a hedging strategy. The model is designed to provide flexibility in practical applications.
Vedoucí práce: Luboš Marek
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: statistika [obor disert. práce]; disertace; dissertations